Program Komunikasi Antar Pribadi (KAP) Sebagai Upaya Keluarga Terhadap Pencegahan Bunuh Diri Pada Remaja di SMP Muhammadiyah 12 Paleran - Yeni Suryaningsih; Hasna’ Huwaida (Jurnal Pengabdian Masyarakat (JUDIMAS), 2025)
Suicide is an attempt by someone to end their life. National Police data recorded 852 cases of suicide from January to August 2024. Case has increased compared to 2023 which was only 300 cases per year, suicide often occurs at the age of 17-25 years. Interpersonal Communication (KAP) is needed to overcome this incident. Purpose of this program to provide education to parents and adolescents about suicide prevention. Program was implemented at SMP Muhammadiyah 12 Paleran, developed in accordance with the community service plan of the University of Muhammadiyah Jember and government policies related to mental health care. Sample of this service is families and adolescents at SMP Muhammadiyah 12 Paleran. Method will be used is Participatory Action Research (PAR) through surveys and needs analysis: suicide prevention education, Interpersonal Communication (KAP) roleplay and family and adolescent assistance. Activity was carried out on February 1-20, 2025 at SMP Muhammadiyah 12 Paleran, attended by 79 adolescents and families. Activities include socialization of activities, suicide prevention education, roleplay of Interpersonal Communication (KAP) and mentoring of adolescents and families. Conclusion of the results obtained 100% of families expressed satisfaction with the Interpersonal Communication (KAP) program as evidenced by the majority of families wanting similar activities to be held at SMP Muhammadiyah 12 Paleran. So this program can be continued. Keywords: Interpersonal Communication (KAP), Prevent suicide, Adolescents